Hubungan Pengetahuan dan Sikap Upaya Pencegahan Tubercolosis (TBC) di Wilayah Kerja Puskesmas Geureudong Pase Aceh Utara - Muslim Amin; Ahmad Fausi (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
This study examines the relationship between knowledge and attitudes towards tuberculosis (TB) prevention efforts in the working area of the Geureudong Pase Health Center. An observational study with a case control design was conducted during the period September–November 2024, involving 31 respondents. The characteristics of the respondents showed that the majority were 21 years old (69.8%), male (37.0%), had an elementary education (36.7%), and worked as farmers (76.6%). Data analysis includes univariate and bivariate analyses. Univariate analysis was carried out descriptively using a frequency distribution table to see the distribution of respondent characteristics and research variables. Meanwhile, bivariate analysis uses chi-square tests to determine the relationship between knowledge and attitudes and TB prevention efforts. The results of the study show that the level of knowledge has a significant impact on TB prevention efforts. Of the 30 well-informed respondents, only 1 respondent (3.8%) actually made effective prevention efforts. In contrast, as many as 25 respondents (96.2%) with a low level of knowledge had less prevention efforts. In addition, only 4 respondents (13.8%) had good prevention efforts overall. Statistical tests proved that there was a significant relationship between knowledge (p=0.000) and attitudes (p=0.000) towards TB prevention efforts. These findings show the need for educational interventions to increase public knowledge about TB and increase positive attitudes towards its prevention. Thus, increasing socialization and health education is an important step in efforts to control TB in the region.